The Influence of Non-Physical Work Environment, Discipline, and Motivation on Teacher Performance in Deli Serdang - Farida, Farida; Pradiani, Theresia; Ruspitasari , Widi Dewi (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to examine the influence of the work environment and work discipline on teacher performance, with work motivation serving as a mediating variable at the Pelita Intelektual Foundation in Deli Serdang. A quantitative approach was applied, utilizing path analysis through Partial Least Squares Structural Equation Modelling (PLS-SEM). The study involved a total of 96 teachers as the research population, using total sampling. The results indicate that both the work environment and work discipline have a positive and significant effect on teacher performance, both directly and indirectly through work motivation as a mediating factor. Work motivation was found to strengthen the influence of the work environment and work discipline on performance outcomes. These findings underscore the importance of creating a supportive work environment, enforcing work discipline, and continuously fostering teacher motivation to enhance performance. It is recommended that the foundation place greater emphasis on these three factors as part of its sustainable human resource development strategy.